The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/ec.00292-07
|View full text |Cite
|
Sign up to set email alerts
|

Excystation of Eimeria tenella Sporozoites Impaired by Antibody Recognizing Gametocyte/Oocyst Antigens GAM22 and GAM56

Abstract: Eimeria tenella is the causative agent of coccidiosis in poultry. Infection of the chicken intestine begins with ingestion of sporulated oocysts releasing sporocysts, which in turn release invasive sporozoites. The monoclonal antibody E2E5 recognizes wall-forming body type II (WFBII) in gametocytes and the WFBII-derived inner wall of oocysts. Here we describe that this antibody also binds to the stieda body of sporocysts and significantly impairs in vitro excystation of sporozoites. Using affinity chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 43 publications
4
45
0
Order By: Relevance
“…We have recently obtained similar results with both E. tenella and E. acervulina, demonstrating the conservation of these proteins and the process of wall formation (SI Belli et al, unpublished observations). Recently, Krücken et al (2008) have confirmed the presence of two E. tenella homologues of EmGam56 and, additionally, reported the discovery of a 22 kDa antigen in the macrogametocytes of E. tenella. Like the other proteins so far characterized, antibodies to this protein react with WFB2 and the inner layer of the oocyst wall.…”
Section: Proteins Of the Oocyst Wallmentioning
confidence: 86%
See 1 more Smart Citation
“…We have recently obtained similar results with both E. tenella and E. acervulina, demonstrating the conservation of these proteins and the process of wall formation (SI Belli et al, unpublished observations). Recently, Krücken et al (2008) have confirmed the presence of two E. tenella homologues of EmGam56 and, additionally, reported the discovery of a 22 kDa antigen in the macrogametocytes of E. tenella. Like the other proteins so far characterized, antibodies to this protein react with WFB2 and the inner layer of the oocyst wall.…”
Section: Proteins Of the Oocyst Wallmentioning
confidence: 86%
“…It is notable for another reason, namely that its gene is present in extremely high copy number (in contrast to the single copies of the genes for, for example, EmGam56 and EmGam82), indicating that it may be important in oocyst wall formation via a mechanism distinct from that of the tyrosine-rich proteins. As yet, no information is available about whether this 22 kDa protein is processed into smaller polypeptides nor how it is incorporated into the oocyst wall, though its involvement in stabilizing the oocyst wall via cross-links between histidine and catechols, as seen in insect cuticles (Christensen et al 1991, Xu et al 1997, Kerwin et al 1999, is a distinct possibility (Krücken et al 2008). …”
Section: Proteins Of the Oocyst Wallmentioning
confidence: 99%
“…7), and this may have a direct link with the stockpiling and eventual cross-linking of the oocyst wall glycoproteins Gam56 and Gam82 (6,7). It is possible that O glycosylation is required for trafficking of these proteins to the oocyst wall, a hypothesis supported by the conservation of an O glycosylation motif in both EmGam56 and EtGam56 and an additional oocyst wall protein of E. tenella, EtGam22 (19).…”
Section: Discussionmentioning
confidence: 99%
“…EmGam56 and EmGam82 are processed into smaller peptides prior to incorporation into the oocyst wall, where proposed cross-linking occurs to ensure the formation of a stable extracellular matrix (5,6). EtGam56, an E. tenella homologue of EmGam56, appears to undergo a similar process of truncation prior to oocyst wall formation (19,25), implying that this mechanism is strongly conserved within the Eimeria genus.…”
mentioning
confidence: 99%
See 1 more Smart Citation